SEG Technical Program Expanded Abstracts 2012 2012
DOI: 10.1190/segam2012-1468.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Fréchet derivative and its De Wolf approximation

Abstract: SummaryWe introduce and derive the nonlinear Fréchet derivative for the acoustic wave equation. It turns out that the high order Fréchet derivatives can be realized by consecutive applications of the scattering operator and a zero-order propagator to the source. We prove that the higher order Fréchet derivatives are not negligible and the linear Fréchet derivative may not be appropriate in many cases, especially when forward scattering is involved for large scale perturbations. Then we derive the De Wolf appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…This leads to the transmission case in which the incident and scattered slowness vectors are parallel. This corresponds to the forward scattering of the De Wolf approximation (De Wolf ; Wu and Zheng ). We shall also consider a perturbation only smoothed in the horizontal direction that leads to the reflection case over a flat horizontal reflector where the incident and scattered slowness vectors are related through Snell's law.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the transmission case in which the incident and scattered slowness vectors are parallel. This corresponds to the forward scattering of the De Wolf approximation (De Wolf ; Wu and Zheng ). We shall also consider a perturbation only smoothed in the horizontal direction that leads to the reflection case over a flat horizontal reflector where the incident and scattered slowness vectors are related through Snell's law.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng (2012, 2014) introduced the higher order Fréchet derivatives and the theory of nonlinear partial derivative (NLPD) operator for the acoustic wave equation. Our previous work (Wu and Zheng 2012, Wu et al 2013 have reported the renormalization procedure using De Wolf series and its approximation to improve the convergence of forward scattering series. In this paper we will report the progress in removing the divergence of inverse Born T-series by renormalization procedure and the derivation of the inverse thin-slab propagator (ITSP).…”
Section: Introductionmentioning
confidence: 99%